2007
DOI: 10.1128/jvi.01220-06
|View full text |Cite
|
Sign up to set email alerts
|

Absence or Overexpression of the Varicella-Zoster Virus (VZV) ORF29 Latency-Associated Protein Impairs Late Gene Expression and Reduces VZV Latency in a Rodent Model

Abstract: Varicella-zoster virus (VZV) ORF29 encodes the viral single-stranded DNA binding protein and is expressed during latency in human ganglia. We constructed an ORF29 deletion mutant virus and showed that the virus could replicate only in cells expressing ORF29. An ORF29-repaired virus, in which ORF29 was driven by a cytomegalovirus promoter, grew to peak titers similar to those seen with the parental virus. The level of ORF29 protein in cells infected with the repaired virus was greater than that seen with parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…This suggestion follows from the findings of Cohen et al (11), who found that the overexpression of the ORF29 protein impaired the establishment of latency in a rodent model. Some limited replication of VZV is believed to occur in DRG neurons prior to the establishment of latency, resulting in the presence of multiple copies of the viral genome per neuron (27).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This suggestion follows from the findings of Cohen et al (11), who found that the overexpression of the ORF29 protein impaired the establishment of latency in a rodent model. Some limited replication of VZV is believed to occur in DRG neurons prior to the establishment of latency, resulting in the presence of multiple copies of the viral genome per neuron (27).…”
Section: Discussionmentioning
confidence: 75%
“…The ORF29 protein is believed to be essential for the initiation of viral DNA replication by analogy with ICP8 (20,30). ORF29 transcripts and protein have been reported to be present in latently infected human dorsal root ganglion (DRG) neurons (36), and ORF29 is involved in the establishment of latency in the cotton rat model (11).…”
mentioning
confidence: 99%
“…VZV ORF 18 encodes the small subunit of ribonucleotide reductase, an enzyme critical to synthesis of DNA precursors, and also protects neurons from apoptotic cell death (34). VZV ORF 21 encodes a nucleocapsid protein (29), and VZV ORF 29 encodes a DNA binding protein that is essential for virus replication (4,31). VZV ORFs 40 and 68 encode virus structural proteins.…”
Section: Discussionmentioning
confidence: 99%
“…DNA encoding all 4 of the ORFs examined was detected at 28 days in both the colon and ileum in each of 4 guinea pigs; nevertheless, transcripts encoding ORFs 40 and 67 could not be detected in 3 of the 4 animals. Transcripts encoding ORFs 29 and 66, however, which encode genes transcribed during latency (Chen et al , 2011; Cohen et al , 2007; Cohrs et al , 2003; Folster et al , 2011; Grinfeld and Kennedy, 2004; Sato et al , 2003b; Stallings et al , 2006), were found in the colon and ileum of all 4 guinea pigs. These observations are consistent with the idea that VZV established enteric latency in 3/4 guinea pigs and that an asymptomatic lytic infection, associated with the expression of ORFs 40 and 67, was present in the bowel of 1 of the 4 animals.…”
Section: Resultsmentioning
confidence: 97%